Telomere in Cancer Development - Nan, PhD, Hongmei (North American Journal of Medicine and Science, 2010)
Telomeres are long hexameric (TTAGGG)n repeats at the ends of the p and q arms of linear eukaryotic chromosomes. Telomeres play a critical role in maintaining the structural integrity of chromosomes by preventing fusion of chromosomal ends, nucleolytic decay, end-to-end fusion, and atypical recombination. Telomere length in peripheral blood lymphocytes (PBLs) has emerged as a potential biomarker of aging and risk of age-related diseases such as cancers. Telomere length is a complex trait that is shaped by genetic and environmental determinants. In this review, we summarize the previous studies on the association of telomere length and telomere-related genetic variants with the risk of various cancers.